Riding Through the Pandemic: Unveiling Motorcycle Crash Trends Amidst Three Years of the COVID-19 Crisis - Shahrin Islam; Armana Sabiha Huq; Sadab Ishraq Khan; Sabah Hossain Iqra (Journal of Advanced Transportation)
Bangladesh has a significant prevalence of motorcycle usage accompanied by a correspondingly high incidence of motorcycle-related fatalities. The COVID-19 crisis has brought additional challenges to road safety in Bangladesh because of containment strategies and restrictions. The impacts of the pandemic on motorcycle-related road traffic crashes, injuries, and fatalities in Bangladesh are investigated in this study using ARIMA time series analysis. Data spanning 86 months (January 2016 to February 2023) were collected from the Accident Research Institute (ARI), which compiles newspaper-based data serving as an alternative source of information on crashes encompassing both pre-COVID (January 2016 to February 2020) and COVID-19 periods (March 2020 to February 2023). Three COVID-19 waves were demonstrated, with the first wave showing a significant decrease in crashes, injuries, and fatalities due to a government-imposed lockdown. During the second wave, crashes and fatalities approached predicted values, while injuries remained lower than anticipated. The third wave witnessed a sudden drop, followed by a sharp rise in all three variables. Box and whisker plot analysis confirmed the disparities between observed and predicted values, with observed data being lower. These results demonstrate the significant impact that COVID-19 containment strategies have had on trends in motorcycle crashes. By understanding these patterns, policymakers and road safety authorities can develop adaptive interventions to mitigate motorcycle-related incidents during pandemics or similar crises. The study provides a data-driven foundation for designing context-specific policies, adjusting law enforcement strategies, and efficiently allocating resources to enhance road safety under varying conditions.